Developing a multidisciplinary approach within the ED towards domestic violence presentations. Issue 3 (23rd January 2013) - Basu, Subhashis; Ratcliffe, Giles
Abstract : Aim: To improve the detection and quality of care of patients who attend the emergency department (ED) with confirmed or suspected domestic abuse (DA). Design: A quality improvement report on the design, implementation and evaluation of a specialised service and structured training programme to detect and manage DA presentations within an emergency medicine department. Setting: The study was set in the ED at the Northern General Hospital, Sheffield, UK. Key measures for improvement: Key measures for improvement included introducing a service within the ED to help staff manage DA and coordinate responses; improve staff confidence in detecting DA; develop a structured and consistent process by which to manage DA presentations. Strategies for change: An Independent Domestic Violence Advocate service was introduced into the department in July 2011 through a multiagency agreement. A structured training and education programme was delivered to ED staff. A 'communications form' was developed for DA risk assessment and case management. The process was reviewed quarterly. Results: One hundred and seventy-two referrals were made to the service (121 distinct clients) over a 12-month period. Staff reported greater confidence in detecting DA, and community partners highlighted the role the service had in improving DA detection and care quality within the city. Conclusions: Strong leadership and prioritising the issue within the department has facilitated the development of the process and contributed substantially to its success. Support from community partners has been invaluable in tailoring the service and education programme to the needs of staff and patients within the department.